The Effects of a Low-Carbohydrate Diet on Glycemic Control and Weight in Patients with Type 2 Diabetes Mellitus: Literature Review - Tri Budi Julianti; Tania Putri; Dewi Lutfania Syahrani; Javier Ammar; Siti Khadijah; Rizki Nur Azmi (Strada Journal of Pharmacy, 2026)
Type 2 diabetes mellitus (T2DM) is an increasing global health problem characterized by chronic hyperglycemia due to insulin resistance and/or insulin secretion deficiency. T2DM management often focuses on glycemic control and weight loss through lifestyle interventions, including diet. Low-carbohydrate diets (LCDs) have been one of the most debated and researched dietary interventions, with claims of improving glycemic control and facilitating weight loss. This literature review aims to synthesize the current scientific evidence on the effect of DRK on glycemic control (HbA1c, fasting glucose) and weight in T2DM patients. A systematic review method will be used to identify, evaluate and summarize relevant studies from electronic databases. The review will present key findings from studies, discuss underlying mechanisms, and identify potential benefits, risks, and limitations of DRK. This literature review is expected to provide a more comprehensive understanding for clinical practitioners, patients, and researchers in considering DRK as a T2DM management strategy.